Cerita Pedanda Baka Sebagai Media Pendidikan Karakter Sejak Anak Usia Dini - Novitasari, Ayuningtyas; Bagus Antara Putra, Anak Agung Gede (Jayapangus Press, 2023)
Various media outlets have reported about children's bad behavior lately. Some of the violence committed by against their own friends, lack of respect for parents and teachers, show the bad character of children. teachers, show the bad character of children. This inspired the author to explore the cultures that were used as a medium for shaping children's character by their parents. children's character by their parents. Balinese society has a variety of cultures that can be used as a medium for character education, such as the culture of storytelling for children. Character education throught the Pedande Baka story for early childhood is a religious character. The religious character is belief in Ida Sang Hyang Widhi Wasa. In Hinduism, the religious character is explained in the Panca Sradha, including belief in Karma Phala or belief in the result of every human action. Breath, hearbeat and dreams are karma. If we do good, we will get good result, and vice versa. The religious character that can be found in the Pedande Baka story by the crab is a result of Pedande Baka bad behavior. Pedande Baka lied and killed all the fish in the lake. This shows that Pedande Baka receives Prarabdha Karma Phala, which means that actions in this life will also be accepted in this life. Parents can teach religious character by telling them that Pedande Baka bad behavior was paid for by being killed by a crab. Throught this story parents can teach children to do good things such as: being honest, not killing, beleiving in god and Karma Phala. for children, stories are believed to contain character education values for children from an early age. children from an early age. The purpose of this paper is to explore the character values values that can be transferred through the story of Pedanda Baka and how this story can be used as a medium for character education to children from an early age. character education to children from an early age. This article is a literature review literature review. After the review, it was found that the character values that can be educated through the Pedanda Baka story are can be educated through the Pedanda Baka story is religious character. Character education through the Pedanda Baka story is carried out by storytelling to children by parents at home and by teachers at school because the cognitive development of early childhood. at home and by teachers at school because early childhood cognitive development is symbolic behavior, and stories are symbolic in nature. is symbolic behavior, and stories are symbolic. Stories help abstract and intangible concepts become concrete and real. Stories can be used as a medium for character education from an early age, because it helps children imitate the character values contained in the story.